The inheritance - Alexander, Tamera (Women of faith fiction, 2009)
McKenna Ashford moves west with her rebellious younger brother Robert. U.S. Marshall Wyatt Caradon's well-meant attempt to help the young man brings him face-to-face with the one situation he never wanted to encounter--and the one woman who holds the key to helping him find his future.